2012
DOI: 10.1080/15389588.2011.644254
|View full text |Cite
|
Sign up to set email alerts
|

Does Personality Predict Driving Performance in Middle and Older Age? An Evidence-Based Literature Review

Abstract: Overall, we found evidence for personality as a reliable predictor of driving performance among older drivers. However, 2 caveats qualify our conclusions: the research considered only a limited number of personality variables and largely consisted of less valid tests of driving performance. Therefore, to truly understand the relationship between personality and driving performance, future research must consider a wider range of individual differences and employ more stringent tests and methodological designs t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 50 publications
1
18
0
Order By: Relevance
“…The only baseline measures to show significant associations to accidents (unreported to police/insurance companies) were sensation seeking personality and pre-morbid driving violations. From the general population, these are known risk factors of accident involvement [61,65]. However, due to the Poisson distribution of the accident parameters, low sample size and short follow-up time, these numbers must be interpreted within those limitations.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…The only baseline measures to show significant associations to accidents (unreported to police/insurance companies) were sensation seeking personality and pre-morbid driving violations. From the general population, these are known risk factors of accident involvement [61,65]. However, due to the Poisson distribution of the accident parameters, low sample size and short follow-up time, these numbers must be interpreted within those limitations.…”
Section: Discussionmentioning
confidence: 98%
“…Given that the majority of participants who completed the on-road test drove acceptably (81.5%), it is a fair assumption that, in this study, the DBQ in some cases provided additional information of the shared variance between self-regulation and real-life driving behaviours not necessary shown during the on-road driving test. Studies have shown that impulsive personality traits [59] and dysexecutive symptoms [50] are related to aberrant driving behaviours, which in turn are correlated with involvement in accidents [61,64]. In addition, self-regulation and awareness of cognitive capacity are regarded as pre-requisites for tactical and strategic coping strategies during driving [25].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations